Functional Group and Substructure Searching as a Tool in Metabolomics - TIPTON, KEITH; MCDONALD, ANDREW (My University, 2008)
Background: A direct link between the names and structures of compounds and the functional groups contained within them is important, not only because biochemists frequently rely on literature that uses a free-text format to describe functional groups, but also because metabolic models depend upon the connections between enzymes and substrates being known and appropriately stored in databases. Methodology: We have developed a database named ?Biochemical Substructure Search Catalogue? (BiSSCat), which contains 489 functional groups, >200,000 compounds and >1,000,000 different computationally constructed substructures, to allow identification of chemical compounds of biological interest. Conclusions: This database and its associated web-based search program (http://bisscat.org/) can be used to find compounds containing selected combinations of substructures and functional groups. It can be used to determine possible additional substrates for known enzymes and for putative enzymes found in genome projects. Its applications to enzyme inhibitor design are also discussed.
PUBLISHED
Keywords: Biochemistry; BiSSCat